GLOBAL FINANCIAL TRENDS AND CHALLENGES IN THE 21ST CENTURY: A GENERAL OVERVIEW - Urunova Maftuna Gayratovna (Bright Mind Publishing, 2025)
This paper explores the dynamic evolution of global finance in the 21st century, focusing on key trends such as financial digitalization, decentralized finance, risk management innovations, and financial sustainability. It highlights the challenges financial systems face due to economic globalization, technological disruption, and regulatory complexities. The analysis integrates insights from recent studies, institutional reports, and practical cases, offering a balanced perspective on how finance is adapting to a rapidly changing world.
Keywords: Global Finance, Financial Technology (FinTech), Risk Management, Financial Regulation, Decentralized Finance (DeFi), Financial Inclusion, Sustainable Finance, Economic Globalization.